Locally Controllable Attitude B-Spline Function - Young Soo Suh (IEEE Access)
Continuous attitude spline functions are used in computer animation and in the generation of virtual inertial sensor data. Unlike the B-spline functions in $R^{3}$ , it is not easy to locally control attitude the B-spline function in $SO(3)$ . In this paper, a modified attitude B-spline function is proposed, where the local control problem (smoothness and distance between the target attitude and spline function) is formulated as a linear quadratic optimization problem. The proposed algorithm is tested with human attitude target data to demonstrate the local controllability of the attitude B-spline functions.